(untitled) - Brooks, William T. (Hoboken, NJ., 2004)
This book takes a new and relevant approach to sales from the perspective of both organizational and individual performance. Based on the author's broad-based personal experience working with over 2,000 sales organizations, it combines organizational guidelines, sales management strategies, how-to sales tips, and career guidance for sales executives, sales managers, and salespeople alike. Incorporating proprietary research, case studies, real-world examples, and practical information, this book will revolutionize the very way sales organizations sell.
Keywords: Sales management,Selling